Neural Correlates of the Propensity for Retaliatory Behavior in Youths With Disruptive Behavior Disorders - White, Stuart F.; VanTieghem, Michelle; Brislin, Sarah J.; Sypher, Isaiah; Sinclair, Stephen; Pine, Daniel S.; Hwang, Soonjo; Blair, R. James R. (The American journal of psychiatry, 2016)
Objective:Youths with disruptive behavior disorders (DBD) (conduct disorder and oppositional defiant disorder) have an elevated risk for maladaptive reactive aggression. Theory suggests that this is due to an elevated sensitivity of basic threat circuitry implicated in retaliation (amygdala/periaqueductal gray) in youths with DBD and low levels of callous-unemotional traits and dysfunctional regulatory activity in the ventromedial prefrontal cortex in youths with DBD irrespective of callous-unemotional traits.Method:A total of 56 youths 10–18 years of age (23 of them female) participated in the study: 30 youths with DBD, divided by median split into groups with high and low levels of callous-unemotional traits, and 26 healthy youths. All participants completed an ultimatum game task during functional MRI.Results:Relative to the other groups, youths with DBD and low levels of callous-unemotional traits showed greater increases in activation of basic threat circuitry when punishing others and dysfunctional down-regulation of the ventromedial prefrontal cortex during retaliation. Relative to healthy youths, all youths with DBD showed reduced amygdala-ventromedial prefrontal cortex connectivity during high provocation. Ventromedial prefrontal cortex responsiveness and ventromedial prefrontal cortex-amygdala connectivity were related to patients’ retaliatory propensity (behavioral responses during the task) and parent-reported reactive aggression.Conclusions:These data suggest differences in the underlying neurobiology of maladaptive reactive aggression in youths with DBD who have relatively low levels of callous-unemotional traits. Youths with DBD and low callous-unemotional traits alone showed significantly greater threat responses during retaliation relative to comparison subjects. These data also suggest that ventromedial prefrontal cortex-amygdala connectivity is critical for regulating retaliation/reactive aggression and, when dysfunctional, contributes to reactive aggression, independent of level of callous-unemotional traits.